Adherence to the CONSORT statement and extension for nonpharmacological treatments in randomized controlled trials of bariatric surgery: A systematic survey. (4th April 2021) - Liu, Meilu; Chen, Jianrong; Wu, Qingni; Zhu, Weifeng; Zhou, Xu
Summary: Reporting is critical for establishing the value of randomized controlled trials (RCTs). This study evaluated the adherence of bariatric surgery RCT reporting to the CONsolidated Standards Of Reporting Trials (CONSORT) statement 2010 and its 2017 extension for non‐pharmacologic treatments (NPT extension). We identified all RCTs comparing bariatric surgery with conservational therapy or alternative bariatric surgery up to June 30, 2020. Reporting quality was assessed using criteria developed from the CONSORT statement and the NPT extension and scored as a percentage. The factors associated with reporting quality were explored by univariate and multivariate analysis. In total, 102 RCTs of bariatric surgery were included. The median scores according to the CONSORT statement and NPT extension were 63.3 and 26.8 of a maximum possible 100, respectively. Two‐thirds of NPT extension items were reported in less than 25% of the RCTs. The median score improved over time for the CONSORT statement but not the NPT extension. A higher CONSORT score was associated with publication in core clinical journals, protocol registration, and funding. No factors associated with the NPT extension score were identified. Substantial efforts are warranted from authors, journals, registration platforms, and funders to overcome the flaws in the reporting of bariatric surgery RCTs.